Standards of prescription writing in a long-term psychogeriatric unit: a series of clinical audits. (13th October 2014) - Wilson, L. S.; Devitt, P.; Hally, O.
Abstract : Objective: The aim of this study was to improve the quality of prescription writing in a long-term psychogeriatric inpatient unit by a combination of serial audits and interventions designed to address the identified deficiencies. Methods: We undertook three clinical audits of the prescription sheets used in an inpatient unit providing continuing care for residents with severe and enduring mental illness and dementia. Based on the findings of the first audit a set of prescribing guidelines was implemented into the ward. Following the second audit a new prescription sheet was developed. The format of the new prescription sheet was designed to account for the needs of the unit and to adhere to Irish and UK best practise guidelines. Two months after its introduction we undertook a third audit. Results: Completion of the drug sensitivity box increased from 25% at audit one to 100% at audit three. Other specific aspects of prescription writing that had been poor at the beginning of the audit cycle also showed improvement: prescribing of generic psychotropic drugs increased by 69% and inclusion of the prescribers Medical Council Registration Number increased by 78%. However, some basic aspects of prescription writing remained weak such as frequency of drug administration and documentation of the stop/review date for 'as required' medication. Conclusion: The results of this study suggest that clinical audit and feedback can improve the quality of prescriptions in an in-patient setting.